Prinsip Dasar Konstitusi Negara dalam Perspektif Al Quran - Mutiara Fahmi (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2014)
This paper basically moved from efforts to prove scientifically and academically that Islam is a religion that has a complete political doctrine and system state, by means of track and ensure the basic principles of the constitution in the verses of the Koran as the primary source of Islamic law normative approach Islam. This study aims to answer some questions: What are the Basic Principles of State Constitutions contained in Alquran? And verses manasaja containing Basic Principles of State Constitutions in the Koran? This study used a descriptive-analytical method with normative-juridical approach (Shar'ie / fiqh).